Mengintegrasikan Teori Pembelajaran Bermakna dan Konstruktivisme dalam Pembelajaran Sejarah di Era Digital - Huda, Khoirul; Djono, Djono (Jurnal Artefak, 2025)
This research aims to examine the integration of meaningful learning theory with constructivist approaches in 21st century history learning, as well as its implications for the development of students' critical thinking skills. Through a literature review approach, this research analyzes several primary sources that include educational theory, history learning practices, and recent studies on digital learning. The results show that TML and constructive learning have common ground in placing students at the center of active learning, with an emphasis on linking prior knowledge, authentic learning experiences, and critical reflection. In the context of digital history learning, strategies such as interactive advance organizers, collaborative discussions, and the use of digital media are proven to support meaningful learning and stimulate critical thinking. This study recommends the development of an integrative history learning model that combines the principles of TML and constructivism, of course, along with the utilization of digital learning technology.